Comparative genomics and biological characterization of sequential Pseudomonas aeruginosa isolates from persistent airways infection. (December 2015) - Bianconi, Irene; Jeukens, Julie; Freschi, Luca; Alcalá-Franco, Beatriz; Facchini, Marcella; Boyle, Brian; Molinaro, Antonio; Kukavica-Ibrulj, Irena; Tümmler, Burkhard; Levesque, Roger; Bragonzi, Alessandra
Abstract Background Pseudomonas aeruginosa establishes life-long chronic airway infections in cystic fibrosis (CF) patients. As the disease progresses, P. aeruginosa pathoadaptive variants are distinguished from the initially acquired strain. However, the genetic basis and the biology of host-bacteria interactions leading to a persistent lifestyle ofP. aeruginosa are not understood. As a model system to study long term and persistent CF infections, theP. aeruginosa RP73, isolated 16.9 years after the onset of airways colonization from a CF patient, was investigated. Comparisons with strains RP1, isolated at the onset of the colonization, and clonal RP45, isolated 7 years before RP73 were carried out to better characterize genomic evolution ofP. aeruginosa in the context of CF pathogenicity. Results Virulence assessments in disease animal model, genome sequencing and comparative genomics analysis were performed for clinical RP73, RP45, RP1 and prototype strains. In murine model, RP73 showed lower lethality and a remarkable capability of long-term persistence in chronic airways infection when compared to other strains. Pathological analysis of murine lungs confirmed advanced chronic pulmonary disease, inflammation and mucus secretory cells hyperplasia. Genomic analysis predicted twelve genomic islands in the RP73 genome, some of which distinguished RP73 from other prototype strains and corresponded to regions of genome plasticity. Further, comparative genomic analyses with sequential RP isolates showed signatures of pathoadaptive mutations in virulence factors potentially linked to the development of chronic infections in CF. Conclusions The genome plasticity ofP. aeruginosa particularly in the RP73 strain strongly indicated that these alterations may form the genetic basis defining host-bacteria interactions leading to a persistent lifestyle in human lungs.